HUBUNGAN KOMPETENSI KEPRIBADIAN GURU AQIDAH AKHLAK DENGAN MORAL SISWA DI KELAS VII MTs BABUSSALAM BATU KORONG - Rahmat Mulia (Fakultas Agama Islam, 2021)
This study aims to determine the personality competence of Aqidah Akhlak teachers at MTs Babussalam Batu Korong, students' morals at MTs Babussalam Batu Korong, and the relationship between personality competencies of Aqidah Akhlak teachers and students' morals at MTs Babussalam Batu Korong. The population in this study were all students of class VII, amounting to 160 students. Sampling was done by random sampling technique as many as 40 students. The research data were collected through a questionnaire and analyzed using descriptive and correlational analysis techniques using the r Product Moment Correlation formula. Based on the results of data analysis, it can be concluded that the results of the study: The personality competence of Aqidah Akhlak Teachers at MTs Babussalam Batu Korong belongs to the sufficient category with an average value of 61.38. The morale of MTs Babussalam Batu Korong students belongs to category C (enough) with an average score of 63.2. The morals shown by students include: Discipline of praying five times a day in congregation, fasting, likes to read the Qur'an, getting used to starting and ending all activities with prayer, speaking, behaving, and getting along well with others. people, and care for others. The relationship between the personality competence of Aqidah Akhlak teachers and the morals of the students of MTs Babussalam Batu Korong is positive and significant. While the Personality Competence of Aqidah Akhlak teachers has an effect of 18.58% on the morale of the students of MTs Babussalam Batu Korong. This means that the personality competence of the Aqidah Akhlak teacher contributes significantly to the morale of the students of MTs Babussalam Batu Korong.